2002
DOI: 10.1101/gr.224602
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Introns Are Not “Junk”

Abstract: Intron-size distributions for most multicellular (and some unicellular) eukaryotes have a sharp peak at their “minimal intron” size. Across the human population, these minimal introns exhibit an abundance of insertion-deletion polymorphisms, the effect of which is to maintain their optimal size. We argue that minimal introns affect function by enhancing the rate at which mRNA is exported from the cell nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 36 publications
6
84
0
Order By: Relevance
“…First, comparative studies of splicing machineries have pointed out the tempo-spatial features of the different types of introns that all have unique characteristics as we have discussed above in this article and previously elsewhere [6]. Second, evolutionary studies have proven that minimal introns are selected through negative selections on minimal-intron-containing genes and have special sequence contexts in human populations [8,11]. The original design of these experiments is to investigate whether the intron size constraint of human minimal introns is selected in a human population but it has also revealed sequence context relevance [38,11].…”
Section: The Routing Hypothesis Of Intron Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…First, comparative studies of splicing machineries have pointed out the tempo-spatial features of the different types of introns that all have unique characteristics as we have discussed above in this article and previously elsewhere [6]. Second, evolutionary studies have proven that minimal introns are selected through negative selections on minimal-intron-containing genes and have special sequence contexts in human populations [8,11]. The original design of these experiments is to investigate whether the intron size constraint of human minimal introns is selected in a human population but it has also revealed sequence context relevance [38,11].…”
Section: The Routing Hypothesis Of Intron Processingmentioning
confidence: 99%
“…The trend is clear and firm over the vertebrate lineage. Third, minimal-intron-containing genes are a unique group of genes in both functionality and genomic characteristics [6,8,33,34]. We have previously showed that genes with minimal introns tend to play certain housekeeping roles and are enriched on certain chromosomal territories [35].…”
Section: The Unique Distributions Of Minimal Introns and Their Possibmentioning
confidence: 99%
See 1 more Smart Citation
“…6), which corresponds perfectly to the length of the minimal intron (61 bp) in Drosophila (Yu et al 2002). Due to snoRNA or snoRNA cluster containing, the host introns can vary in length from 150 bp to 2 kb.…”
Section: Extensive Utilization Of Introns For Snorna-coding In the Drmentioning
confidence: 99%
“…Commonly, we see a bimodal distribution of intron length with a high peak of short (termed 'minimal length') introns and a much flatter peak of longer introns, ranging up to thousands of base pairs in length in humans (Yu et al, 2002). Furthermore, in some organisms there appears to be a functional link between intron length and gene expression, with introns tending to be smaller in highly expressed genes -possibly as a result of a need for transcriptional efficiency.…”
Section: The Diversity Of Intronsmentioning
confidence: 99%